Efficient march-like algorithm for detection of all two-operation dynamic faults from subclass Sav - H. Avetisyan; G. Harutunyan; V. A. Vardanian (Изд-во НАН РА)
This paper introduces an e±cient March-like algorithm for detection of the well known class Sav of dynamic faults. Sav is the subclass of all two-operation dynamic functional fault models that are sensitized by means of applying two consecutive operations, one applied on the aggressor cell and the second operation applied on the victim cell. Earlier, only subclasses Saa and Svv were considered by a few authors when both sensitizing operations were applied either on the aggressor or victim cell, and March algorithms were developed by them. Subclasses Sav and Sva were not considered due to their complexity. A larger class of March-like algorithms has to be considered for detection of those subclasses since March algorithms cannot detect them. It is shown that 392N operations are su±cient for detection of faults from Sav.
Keywords: Mathematics; Algorithm